2007
DOI: 10.1074/jbc.m701956200
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role for Transcription Coactivator Peroxisome Proliferator-activated Receptor (PPAR)-binding Protein/TRAP220 in Liver Regeneration and PPARα Ligand-induced Liver Tumor Development

Abstract: Disruption of the gene encoding for the transcription coactivator peroxisome proliferator-activated receptor (PPAR)-binding protein (PBP/TRAP220/DRIP205/Med1) in the mouse results in embryonic lethality. Here, we have reported that targeted disruption of the Pbp/Pparbp gene in hepatocytes (Pbp ⌬Liv ) impairs liver regeneration with low survival after partial hepatectomy. Analysis of cell cycle progression suggests a defective exit from quiescence, reduced BrdUrd incorporation, and diminished entry into G 2 /M … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 36 publications
1
63
0
Order By: Relevance
“…23 Proteins associated with signaling pathways of relevance to liver biology (platelet-derived growth factor, interleukin-4, epidermal growth factor, and insulin receptor signaling pathways) were also identified among the proteins common to liver tissue and plasma. They included peroxisome proliferator-activated receptor binding protein, an important player in liver regeneration, 24 epidermal growth factor receptor, involved in the proliferation and mitogenesis of hepatocytes, 25 inositol 1,4,5-triphosphate receptor, which has been found to be decreased in bile ducts of patients with primary biliary cirrhosis, 26 and signal transducer and activator of transcription 2, which promotes antiviral defense in the liver. 27 Finally, 10 members of the A disintegrin and metalloproteinase protein and A disintegrin-like and metalloproteinase with thrombospondin motifs families were identified.…”
Section: Discussionmentioning
confidence: 99%
“…23 Proteins associated with signaling pathways of relevance to liver biology (platelet-derived growth factor, interleukin-4, epidermal growth factor, and insulin receptor signaling pathways) were also identified among the proteins common to liver tissue and plasma. They included peroxisome proliferator-activated receptor binding protein, an important player in liver regeneration, 24 epidermal growth factor receptor, involved in the proliferation and mitogenesis of hepatocytes, 25 inositol 1,4,5-triphosphate receptor, which has been found to be decreased in bile ducts of patients with primary biliary cirrhosis, 26 and signal transducer and activator of transcription 2, which promotes antiviral defense in the liver. 27 Finally, 10 members of the A disintegrin and metalloproteinase protein and A disintegrin-like and metalloproteinase with thrombospondin motifs families were identified.…”
Section: Discussionmentioning
confidence: 99%
“…Following the binding of an exogenously added activator to its LBD, the mobility of PPARa in the nucleus is reduced, mainly due to the recruitment of a larger complex of coactivators (Feige et al, 2005;Tudor et al, 2007). Such a complex has indeed been isolated from rat liver (Surapureddi et al, 2002) and several coactivators associated with PPARa-RXR have been identified such as CBP/ p300 (Dowell et al, 1997;Tudor et al, 2007), PGC-1a (Vega et al, 2000), members of the SWI/SNF chromatin remodelling complexes (Surapureddi et al, 2002) and of Mediator complexes (Jia et al, 2004;Matsumoto et al, 2007). These coregulators mediate the effects of PPARa-RXR at the transcription level through their action on the chromatin and their interactions with the basal transcription machinery (Fig.…”
Section: Mechanism Of Activationmentioning
confidence: 96%
“…anymore [135]. Additionally, the liver specific ablation of TRAP220 attenuated hepatic steatosis induced by the glucocorticoid receptor (GR) agonist dexamethasone [136].…”
Section: Trap220mentioning
confidence: 99%